2004
DOI: 10.1161/01.cir.0000129968.46095.f3
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Cofactor II Is a Novel Protective Factor Against Carotid Atherosclerosis in Elderly Individuals

Abstract: Background-Thrombin plays a crucial role in atherothrombotic changes. Because heparin cofactor II (HCII) inhibits thrombin actions after binding to dermatan sulfate at injured arterial walls, HCII may negatively regulate thrombin actions in vascular walls. We hypothesized that plasma HCII activity is a preventive factor against atherosclerotic changes, especially in elderly individuals who already have atherosclerotic vascular injuries. Methods and Results-Maximum plaque thickness (MPT) in the carotid artery w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 37 publications
6
69
0
Order By: Relevance
“…As a potent inhibitor of thrombin, HCII may help to down-regulate these processes. Takamori, 5 Aihara, 6 and their colleagues observed negative correlations between plasma HCII activity and the severity of restenosis and atherosclerosis in their patients. These important findings will provide the basis for future clinical and experimental work to determine if HCII is involved directly in arterial pathology or whether, like the storks of Copenhagen, it is there for some other reason.…”
Section: See P 2761mentioning
confidence: 88%
See 1 more Smart Citation
“…As a potent inhibitor of thrombin, HCII may help to down-regulate these processes. Takamori, 5 Aihara, 6 and their colleagues observed negative correlations between plasma HCII activity and the severity of restenosis and atherosclerosis in their patients. These important findings will provide the basis for future clinical and experimental work to determine if HCII is involved directly in arterial pathology or whether, like the storks of Copenhagen, it is there for some other reason.…”
Section: See P 2761mentioning
confidence: 88%
“…4 This work provides direct evidence that HCII can have antithrombotic activity in vivo and draws attention to the arterial system as a potential target of action of HCII. Two clinical studies 5,6 reported in Circulation suggest that HCII may help to protect people from in-stent restenosis or carotid artery atherosclerosis. …”
mentioning
confidence: 99%
“…11 Thus, large-scale investigations and cohort studies are required to assess and clarify the prognostic value of plasma HCII activity for cardiac remodeling in the general population. In addition, it is crucial to compare plasma HCII activities in subjects with and without LV systolic dysfunction for understanding the pathophysiological roles of HCII in cardiac remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…As HCII can counteract the actions of thrombin at injured vascular walls, we, and others, have investigated and confirmed the protective role of HCII against atherosclerosis in clinical examinations and studies using HCII-deficient mice. [9][10][11][12][13][14][15] As the development of vascular remodeling, including atherosclerosis, has been shown to be closely associated with cardiac remodeling in humans and experimental animal models, we hypothesized that HCII is involved in the process of not only atherosclerosis, but also cardiac remodeling. In order to clarify this issue, we investigated the relationships between plasma HCII activity and surrogate markers with respect to cardiac remodeling in elderly subjects with cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a possibility that HC can attenuate the progression of atherosclerosis by inhibiting thrombin action at the injured peripheral arteries. We previously reported an elderly woman with congenital HC deficiency who manifested multiple atherosclerotic disorders 25) , and we have reported the results of clinical studies showing that HC can reduce in-stent restenosis after percutaneous coronary intervention and reduce plaque formation in the carotid artery [26][27][28] . Moreover, we and Tollefsen's group have reported that prominently accelerated vascular remodeling, including atherosclerosis, was observed in HC -deficient mice compared to HC wild-type mice 29,30) .…”
Section: Introductionmentioning
confidence: 99%